2014
DOI: 10.6007/ijarbss/v4-i8/1121
|View full text |Cite
|
Sign up to set email alerts
|

Role of Livestock in Food Security: An Ascertainment from Punjab Pakistan

Abstract: Livestock production plays a major role in the life of farmers in developing countries like Pakistan. As crops and livestock rearing in rural areas directly affects food security condition of the nations. This study has been devised to observe the impact of Livestock on food security. In this regard data was collected from Food Insecurity Report 2009 (SDPI, SDC and World Food Program 2009), Punjab Development Statistics (Government of Punjab 2009) and Agriculture Census Report 2010 (Government of Punjab 2010).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…In recent years, FMD control has been particularly focused on Punjab province, the most populous province in Pakistan for both people and livestock, with relatively developed agricultural systems (11). In February 2020, a workshop in Pakistan, facilitated by the authors of this study and supported by FAO, indicated considerable interest in the creation of an export zone in Bahawalpur Division.…”
Section: Introductionmentioning
confidence: 94%
“…In recent years, FMD control has been particularly focused on Punjab province, the most populous province in Pakistan for both people and livestock, with relatively developed agricultural systems (11). In February 2020, a workshop in Pakistan, facilitated by the authors of this study and supported by FAO, indicated considerable interest in the creation of an export zone in Bahawalpur Division.…”
Section: Introductionmentioning
confidence: 94%
“…Livestock farming and its industry represents an important and key component of the agricultural economy especially among least developed and developing countries. Livestock farming contributes beyond direct food production which shares multipurpose provisions which include animal skins, fiber, fertilizers and fuels, and also capital accretion ( Mahmood et al, 2014 ). In addition, livestock farming is are intimately associated with the social and cultural values of millions of resource-poor communities where livestock possession assures sustainable agricultural farming and economic stability.…”
Section: Flaws Gaps and Limitations In Climate Change And Food Securi...mentioning
confidence: 99%
“…Contribution of livestock products to the food security of rural and urban people is significant in south Asian countries like Pakistan, India, Bangladesh and China. Moreover, Balehegn et al (2020) mentioned that livestock sector in India is supplying nutritional security to the fast-growing population and Mahmood et al (2014) stated the positive relationship between the milk and animal per person, work animal per hectare and food safety in Pakistan. Similarly, the possible influence of livestock possession on food security of individual households in Pakistan was calculated using the propensity score matching approach by Ali and Khan (2013) and results indicated that level of food security was higher for the households having livestock as compared to households having no livestock.…”
Section: Introductionmentioning
confidence: 99%